The role and regulatory mechanism of miR-122-5p in the process of pilon fracture healing - Yang Zhang; Yingnan Li; Min Zhou; Lichang Yang (Journal of Orthopaedic Surgery and Research)
Abstract Objective To explore the role and mechanism of miR-122-5p in the process of fracture healing following a Pilon fracture, as well as to further assess the clinical significance of this molecule as a potential diagnostic marker for fracture nonunion. Methods The expression levels of miR-122-5p were examined in patients with Pilon fracture healed and nonunion, respectively. ROC analysis was employed to evaluate the diagnostic value of miR-122-5p in identifying fracture nonunion, while logistic regression identified its risk factors. The effects of miR-122-5p on the proliferation, apoptosis, and osteogenic differentiation markers of osteoblasts were analyzed by CCK-8 assays, flow cytometry, RT-qPCR, and ALP assay kit. Additionally, DLR and RIP assays validated miR-122-5p targeting PDCD4. Results Serum miR-122-5p was significantly under-expressed in patients with fracture nonunion, whereas PDCD4 exhibits a notable over-expressed. Serum miR-122-5p can predict non-union of fractures, with a sensitivity of 90.82% and a specificity of 78.33%. Low miR-122-5p expression is a potential risk factor for fracture nonunion. The overexpression of miR-122-5p enhanced the proliferation ability of osteoblasts, inhibited cell apoptosis, and upregulated the expressions of ALP, OCN, and RUNX2; knockdown of miR-122-5p elicits opposite effect. PDCD4 is a direct target of miR-122-5p. The osteoblast dysfunction induced by miR-122-5p inhibitors can be reversed by down-regulating PDCD4. Conclusion Diminished miR-122-5p emerge as a potential prognostic indicator for nonunion in Pilon fractures. miR-122-5p accelerates the healing of Pilon fractures by targeting and inhibiting PDCD4.